2011
DOI: 10.1248/yakushi.131.171
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H<sub>1</sub> Receptor Gene as an Allergic Diseases-sensitive Gene and Its Impact on Therapeutics for Allergic Diseases

Abstract: Therapeutics targeting disease-sensitive genes are required for the therapy of multifactorial diseases. There is no clinical report on therapeutics for allergic disease-sensitive genes. We are focusing on the histamine H 1 receptor (H1R) as a sensitive gene. H1R mediates allergy histamine signals. H1R is a rate-limiting molecule of the H1R signal because the signal is increased with elevated receptor expression level. We discovered that the stimulation of H1R induced H1R gene expression through PKCd activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, H1-antihistamines can reduce the proinflammatory cell expression and accumulation of eosinophils and neutrophils (18). It has been showed that the expression of the H1-histamine receptor affects the severity of AR and that the expression of the H1-histamine receptor messenger ribonucleic acid (mRNA) in AR is increased (9). In addition, upregulation of the H1-histamine Several studies reported the association of AR with IL-4 gene polymorphisms in ethnically and geographically distinct populations.…”
Section: H1-antihistamines In Interleukin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, H1-antihistamines can reduce the proinflammatory cell expression and accumulation of eosinophils and neutrophils (18). It has been showed that the expression of the H1-histamine receptor affects the severity of AR and that the expression of the H1-histamine receptor messenger ribonucleic acid (mRNA) in AR is increased (9). In addition, upregulation of the H1-histamine Several studies reported the association of AR with IL-4 gene polymorphisms in ethnically and geographically distinct populations.…”
Section: H1-antihistamines In Interleukin Systemmentioning
confidence: 99%
“…This process is determined by the variation in gene expression. Study by Mizuguchi et al (9) showed that the variation in cytokine receptor genes and H1-histamine receptors played an important role in the pathogenesis of AR. Hussein et al (10) showed that polymorphisms of Toll-like receptors 2 (TLR-2) and TLR-4 genes were associated with susceptibility to AR.…”
Section: Introductionmentioning
confidence: 99%
“…H 1 R also activates NF-kB through G q11 and G upon agonist binding, while constitutive activation of NF-kB occurs only through the G (Bakker et al, 2001;Leurs et al, 1995;Smit et al, 1999). Recently, it was reported that the stimulation of H 1 R induced H 1 R gene expression through protein kinase C (PKC ) activation, resulting in receptor upregulation (Mizuguchi et al, 2011). …”
Section: Histamine Receptorsmentioning
confidence: 99%